2002
DOI: 10.1016/s0960-9822(02)00722-4
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Scrapie Prion Infectivity by Cell Contact in Culture

Abstract: Cell-mediated infection of target cells in this culture system is effective and requires significantly less PrP(Sc) than infection by a prion preparation. Several lines of evidence indicate that it depends on cell contact, in particular, the activity of aldehyde-fixed infected cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
98
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 28 publications
9
98
0
Order By: Relevance
“…The presence of PrP C in caveolae and interactions between PrP C and caveolin-1 have been reported earlier (6,22,39). Binding of prion proteins to the HS chains of recycling Gpc-1 (24 -28) could contribute to the observed transfer of scrapie prion infectivity by cell-to-cell contact (40).…”
Section: Discussionsupporting
confidence: 54%
“…The presence of PrP C in caveolae and interactions between PrP C and caveolin-1 have been reported earlier (6,22,39). Binding of prion proteins to the HS chains of recycling Gpc-1 (24 -28) could contribute to the observed transfer of scrapie prion infectivity by cell-to-cell contact (40).…”
Section: Discussionsupporting
confidence: 54%
“…It has been reported recently that TSE infectivity can spread through infected cell cultures either by direct cell-to-cell contact (43) or via the release of infectivity into the culture medium (44). Whereas a direct correlation between cell-to-cell spread of TSE infectivity and persistence of infection remains to be established, it is possible that impairment of such a mechanism on a cellular level could account for the resistance of some cells to persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…SMB cells were originally isolated from Chandler strain-infected mouse brain culture [31]. However, Chandler-infected SMB cells can be cured with pentosan sulphate and infected de novo with other mouse-adapted prion strains [13,65]. SN56 is a mouse cholinergic septal neuronal cell line which is permissive to the multiplication of several mouse-adapted prion strains [7].…”
Section: Cell Models Permissive To Experimental Rodent-adapted Scrapmentioning
confidence: 99%
“…infectious brain homogenate) with cultured target cells. However, several independent studies have recently shown that prion transmission is much more efficient when live infected biological material is used as the source of infectivity [39,65,99]. Further investigation into the underlying active biological processes will be necessary to optimise prion transmission to cultured cells.…”
Section: De Novo Infection and Cell-to-cell Dissemination Of Prionsmentioning
confidence: 99%
See 1 more Smart Citation